FAMILY CONSTITUTION UNTUK PT. ARTHA TRIMITRA EXPOTAMA - Cahyadi, Hadi; Rich, Kelly; Ovelia (Jurnal Serina Abdimas, 2023)
PT Artha Trimitra Expotama is a company engaged in interior contractors and international exhibitions located in Jakarta and has become a trusted partner of global brands such as Sony, Asus and Samsung. Bylaws, family endowment, investment, distribution of funds, philanthropy, and counterparts. ART, are the rules or guidelines that underlie the implementation of the budget in a family, organization or business. Management, Investment and administration of the Family Endowment Fund shall be managed centrally through the family office, which office will be supervised by an Executive Member and authorized to take all appropriate actions necessary to implement the policies and strategies regarding Family Endowments. PKM implemented using the FGD method is a method and technique of collecting data or information that was originally developed in marketing research. FGD is used to find out the implementation of the company's household budget. By using FGDs, in a relatively short time (quickly) one can explore perceptions, opinions, attitudes, motivations, knowledge, problems and expectations for changes related to certain issues. The achievement target of this community service activity is to increase PT Artha Trimitra Expotama's ability to implement the Bylaws in the company's costs and increase profitability. We plan to carry out this series of activities from August 2022 – December 2022. PT Artha Trimitra Expotama adalah sebuah perusahaan yang bergerak dibidang kontraktor interior dan pameran internasional yang berada di Jakarta dan sudah menjadi mitra terpercaya dari merek global seperti Sony, Asus dan Samsung. Anggaran Rumah Tangga, family endowment, investas, distribusi dana, filantropi, dan counterparts. ART, adalah peraturan atau pedoman yang mendasari pelaksanaan anggaran dalam sebuah keluarga, organisasi, atau bisnis. Manajemen, Investasi dan pengelolaan Dana Abadi Keluarga harus dikelola secara terpusat melalui kantor keluarga, kantor mana yang akan diawasi oleh Anggota Eksekutif dan berwenang untuk mengambil semua tindakan yang sesuai yang diperlukan untuk menerapkan kebijakan dan strategi mengenai Pemberkahan Keluarga. PKM dilaksanakan dengan metode FGD merupakan metode dan teknik pengumpulan data atau informasi yang awalnya dikembangkan di dalam penelitian pemasaran. FGD digunakan untuk mengetahui implementasi anggaran rumah tangga perusahaan. Dengan menggunakan FGD, dalam waktu relatif singkat (cepat) dapat digali mengenai persepsi, pendapat, sikap, motivasi, pengetahuan, masalah dan harapan perubahan berkaitan dengan masalah tertentu. Target capaian dari kegiatan pengabdian masyarakat ini adalah peningkatan kemampuan PT Artha Trimitra Expotama dalam melakukan implementasi Anggaran Rumah Tangga dalam perusahaan biaya dan meningkatkan profitabilitas. Serangkaian kegiatan ini kami rencanakan akan dilakukan mulai bulan Agustus 2022 – Desember 2022.